The Influence of Social Media Marketing On Customer Engagement and Purchase Intention: Amor Tien Case Study - Shifa Syafira Rachmat; Atik Aprianingsih (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The growth of the digital fashion industry in Indonesia has concentrated the social media as a key consumer interaction and buying behavior platform. However, there is a decreasing number of interactions with the audience and fluctuations in purchase intention, despite a regular posting schedule, which Amor Tien has experienced. This research clarifies how the contents quality, the interactiveness, and emotional trust affect customer engagement and the mediating effect of engagement on purchase intention on the Instagram media. It is the mixed-method design, which involved a quantitative survey of 250 female Instagram users aged 18-35 years, a quantitative survey, and qualitative evaluation based on the content analysis and platform statistics. An analysis of the data was done using a partial least squares structural equation modelling (SEM-PLS) process. The findings prove that each of the investigated variables has a statistically significant positive impact on customer engagement, which consequently has a strong impact on the purchase intention. The study therefore suggests that the Instagram strategy should be optimized to include interactive, trustworthy, and constant content. In the case of Amor Tien, particularly the improvement of emotional communications, the creation of community-based interaction, and the usage of narrative-based content are essential to intensifying the engagement and maintaining sales growth in the long term.